2013
DOI: 10.1590/s0100-736x2013001100004
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma agalactiae in semen and milk of goat from Pernambuco state, Brazil

Abstract: In goat and sheep flocks, mycoplasmosis is a disease that may cause severe economical losses associated with polyarthritis, mastitis, agalactia, conjunctivitis, pneumonia and reproductive failure. The latter may involve repeat breeding, granular vulvovaginitis, infertility and abortions. The aim of the present study was to assess the occurrence of Mycoplasma agalactiae (Ma) in semen and milk samples from naturally infected goat in the semiarid region from Pernambuco State, Northeast from Brazil. Thirty-nine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
3
1
6
Order By: Relevance
“…This difference may be due to the number of animals and herds used in the survey, to the acquisition of animals from other regions of Brazil and to differences in handling between farms, since the studies were done in different farms, although some municipalities were the same. In the present study, a higher prevalence was observed in goat milk rather than that found by Alves et al(2013) in the State of Pernambuco, which was of 3.7% (3/81). These same authors explain that the difference between the prevalence values is due to the different stages of mycoplasmosis in the herds studied.…”
Section: Resultscontrasting
confidence: 75%
“…This difference may be due to the number of animals and herds used in the survey, to the acquisition of animals from other regions of Brazil and to differences in handling between farms, since the studies were done in different farms, although some municipalities were the same. In the present study, a higher prevalence was observed in goat milk rather than that found by Alves et al(2013) in the State of Pernambuco, which was of 3.7% (3/81). These same authors explain that the difference between the prevalence values is due to the different stages of mycoplasmosis in the herds studied.…”
Section: Resultscontrasting
confidence: 75%
“…M. mycoides subsp mycoides "Small Colony" (MmmSC) e M. (AYLING et al, 2004;DAMASSA et al, 1992;LORIA et al, 2003;NICHOLAS, 2002;NICHOLAS et al, 2008). Em geral, as micoplasmoses mais importantes em pequenos ruminantes possuem alta morbidade e mortalidade (ALVES et al, 2013;BROOKS, 1992;DE AZEVEDO et al, 2006;KINDE et al, 1994).…”
Section: Figura 1 -Distribuição Da Produção De Caprinos No Brasil Em unclassified
“…Posteriormente,Bandeira et al (2008), evidenciaram a presença desse micro-organismo também na Paraíba em 20% dos rebanhos de caprinos detectados por PCR em amostras de leite. Em Pernambuco,Alves et al, (2013) detectaram DNA de M. agalactiae em amostras de sêmen (17,9%), leite (3,7%) de caprinos naturalmente infectados e em amostras de sêmen congelados de centros de inseminação artificial (26,9%). Não foi evidenciado nenhum sinal clínico associado à AC nos animais, assim como, não havia alteração nas análises de qualidade, atividade e motilidade do sêmen, indicando um possível processo crônico ou doença subclínica(ALVES et al, 2013).…”
unclassified
See 2 more Smart Citations